Morphological survey of the burrows of the ghost crab Ocypode rotundata (Miers, 1882) in the southwestern Qeshm Island - M. Naderi; F. Pishehvarzad (‬‭Majallah-i ̒Ilmī-i Shīlāt-i Īrān, 2019)
In this study burrowing behavior of Ocypode rotundata investigated on southwest beaches of Qeshm Island, Persian Gulf, Iran, from February 2015 to January 2016. 9 shapes were recognized which included: single tube burrows, J-shaped, y-shaped with a short branch, y-shaped, spiral burrow, complex burrows, anchor-shaped, J-shaped with two branches, y-shaped with two branches. According to results, single tube burrows, J-shaped, y-shaped and spiral burrow observed in all of seasons whilst, complex burrows observed just during spring to summer. Distribution of burrows occurred in foreshore and backshore studied zone. With crossing of foreshore to backshore, diameter, length and depth of burrows increased while, abundance of burrows showed reduction in number. On the other hand, results showed that male crabs would like to dig J-shaped, spiral and complex burrows. Conversely, built y-shaped burrows in female crabs were more than male crabs. However, crabs of both sexes were found in single tube burrow with similar proportion in the present study.